Environmental Conditions of Food Preparation Areas in University Catering Units in Kenya - Onyuna, A. A. (Africa Environmental Review Journal, 2018)
Environmental conditions are crucial in any food preparation area owing to the sensitive nature of food and its effects on human health if not handled well. Good environmental condition in food preparation areas can result in higher productivity, faster service, more economical working, and most of all, better quality of food. The purpose of this study was to assess environmental conditions of kitchens in University catering units. Seven catering units of Moi University within Eldoret town in Kenya were targeted. A qualitative approach using exploratory research design was adopted. An observation schedule was used to collect data through non-participant observation. Census sampling of the seven catering units of Moi University formed the unit of analysis. A dichotomous scale with “yes and no” options were used to score the aspects that were used to measure prevailing conditions in the kitchens. Cronbach’s Alpha used to test reliability of the items found the significance level at 0.7. Descriptive statistics, factor analysis and Pearson correlation were used to analyse data. Results from factor analysis indicated that out of twenty five items used to measure environmental conditions of food preparation areas, only six components were extracted. The six components include physical aspects, fittings made in the kitchen, arrangement aspects in the kitchen, the atmosphere in the kitchen, provisions considered for the kitchen and cleanliness aspects. Pearson correlation measured the degree of the relationships between and six components which showed that all the relationships tested were not significant except for the relationship between physical aspects and atmosphere